Disease severity and quality of life in patients with psoriasis: Special focus on hepatic panel - Chatterjee, Kingshuk; Mukherjee, Shatavisa; Bera, Deep Kumar; Goswami, Rik (Journal of Pakistan Association of Dermatologists, 2024)
Objective To assess the disease severity and QoL in ambulatory psoriasis patients in a tertiary care set-up, with a special focus on their hepatic profile. Â Methods The study included adult patients clinically diagnosed with psoriasis. Sociodemographic data, disease duration, psoriasis severity, complete hepatic functions were noted. Psoriasis severity and QoL were assessed using Psoriasis Area and Severity Index (PASI) and Dermatology Quality of Life Index (DLQI). Data was statistically analyzed. Â Results Â Mean duration of disease was noted to be 4.85 years among the study population. Mean PASI score observed was 15.04Â±11.41, while the mean DLQI score was 4.97Â±3.13. The psoriasis flare was seen in significantly increasing mark for the initial 20 years, followed by later steep decline. QoL however did not show any abrupt changes over the years. Both psoriasis severity and QoL were positively associated with SGOT, SGPT and albumin levels. PASI and DLQI score were both positively correlated with duration of disease (r=0.69, p<0.05). Psoriasis severity and QoL were also found to have significant positive association, suggesting poorer QoLwith increased disease severity (r=0.268, p=0.001). Â Conclusion Disease severity has been the sole significant predictor of impaired QoL in psoriasis. The study however did not observe significant hepatic abnormalities in the cohort of subjects. Periodic monitoring and treatment of associated conditions can help to achieve better patient outcomes in these chronic treatment scenarios. Â